Strategi pengembangan ekowisata mangrove Bandar Bakau Dumai, Riau - Aras Mulyadi; Efriyeldi Efriyeldi; Burhan Marbun (Universitas Riau, 2021)
Bandar Bakau Mangrove Ecotourism is one of the most attractive natural tourist destinations in Dumai City. As a reference for future development, this study aims to analyze the mangrove ecotourism development strategy of Bandar Bakau Dumai. Surveys to collect primary data have been carried out in the field and on managers of Bandar Bakau Mangrove Ecotourism in June - November 2020. Meanwhile, secondary data were collected from the Dumai City Government and related literature. The data collected were analyzed descriptively, and to formulate a development strategy carried out using a SWOT analysis approach (Strengths, Weaknesses, Opportunities, Threats) from the identification of Internal factors (IFAS) and external factors (EFAS). To make mangrove ecotourism in Bandar Bakau Dumai a natural tourism place that can compete in the future, 4 (four) development strategies have been formulated, namely: 1) Development of Supporting and Supporting Facilities for Mangrove Ecotourism in Bandar Bakau Dumai, 2) Development of Mangrove Ecotourism Products in Bandar Bakau Dumai, 3) Strengthening the Role of Stakeholders in the Development of Mangrove Ecotourism in Bandar Bakau Dumai, and 4) Development of Conservation and Environmental Mitigation of Mangrove Ecotourism in Bandar Bakau Dumai.